Dyplomacja Francji: ewolucja relacji na osi władzy Elysée–Matignon w układzie koabitacji - Kuczyńska, Anna (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2012)
The paper analyzes the decision-making process with respect to foreign policy and defense in the French Fifth Republic. The author discusses the constitutional rights of the President, Prime Minister and Parliament to emphasize that the notion of the exclusive domain (domaine réservé) of the head of the state has no legal grounds. In particular, she stresses the variations in the practice of exercising power in these terms under two distinct political situations: when the president and government are from the same political option, and when they are not. She notes that given the political homogeneity of the President and the majority in the National Assembly, the President, as the actual head of the unified party, becomes the focal point in the creation and implementation of the policies for ‘his’ France, in particular of the country’s foreign policy. This defies the stipulations of Articles 20 and 21 of the Constitution, by virtue of which the government, headed by the Prime Minister, “determines and conducts the policy of the nation.” The paper devotes considerable space to an analysis of the political influence of cohabitation, i.e. the coexistence of a President of the Republic and a majority in the National Assembly who represent different political orientations. This characterized the political system of France for nine years (1986–1988, 1993–1995, 1997–2002) during the evolution of the actual dependency on the Presidential and Prime Ministerial power axis (or the Elysée–Matignon axis, as these state organs are commonly referred to) in the process of shaping and conducting the international and European policy of the state. The role of the Minister of Foreign Affairs is taken into account regarding the outcome of these changeable relations.
French diplomacy: the evolution of relations along the Elysée–Matignon power axis in the cohabitation system